The effect of age and disease duration on the efficacy of subthalamic nuclei deep brain stimulation in Parkinson's disease patients. (7th September 2022) - Du, Tingting; Yuan, Tianshuo; Zhu, Guanyu; Ma, Ruoyu; Zhang, Xin; Chen, Yingchuan; Zhang, Jianguo
Abstract: Background: Previous studies have reported the effects of age and disease duration on the efficacy of subthalamic nuclei deep brain stimulation (STN‐DBS) of Parkinson's disease (PD) patients. However, available data involving these issues are not consistent. In particular, the effect of age and disease duration on the initial efficacy of STN‐DBS has not been established. Methods: A total of 51 patients with PD treated with bilateral STN‐DBS were involved in the present study. They received clinical symptom evaluation during the preoperative, initial, and chronic stages of surgery. The correlations between age when undergoing surgery/age at disease onset/disease duration and outcomes of STN‐DBS were measured. Results: The preoperative levodopa response was negatively associated with age. During the initial stage, the age when undergoing surgery and age at disease onset were negatively correlated with the effect on bradykinesia, with better symptom control of general symptoms in long‐term disease patients. Similarly, patients with an early time of surgery and disease onset and long‐term disease duration showed better control of bradykinesia and axial symptoms at the chronic stage. Furthermore, a long‐term disease duration and early disease onset benefited from an increase of therapeutic efficacy in general, rigid, and axial symptoms with STN‐DBS after a long period. Nevertheless, patients with late disease onset achieved a better relief of stigma. Conclusion: Age and disease durations played a unique role in controlling the symptoms of PD patients treated with STN‐DBS. These results may contribute to patient selection and adjustments of expectations of surgery, based on the age, disease duration, and different symptoms. Abstract : The relationship between alleviation of motor impairment and disease duration. The disease duration had a positive effect on elevation of stimulation (A) and optimal (B) effect on motor impairment between the initial and chronic stages.